"Go upstream, young man": lessons learned from the p38 saga. (7th December 2009) - Hammaker, D; Firestein, G S
Abstract : Despite the success of biological therapies in rheumatoid arthritis (RA), orally active small-molecule drugs are desirable. Signal transduction inhibitors have been the focus of intense efforts, with some recent notable successes and failures. p38α is a signalling molecule that regulates proinflammatory cytokines, which makes it a logical target for RA. Unfortunately, selective p38α inhibitors have limited efficacy. An attempt is made here to put these studies into perspective and offer possible explanations for the failure of p38α blockers. Alternative strategies, such as targeting kinases higher in the signalling cascade or using less selective compounds, might be more successful as suggested by the efficacy seen with Syk and JAK inhibitors.